Pengaruh Sales Growth, Tax Planning dan Tax Avoidance Terhadap Firm Value Pada Sektor Consumer Non-Cyclicals Di Bursa Efek Indonesia - Ardiani, Irma; Situngkir , Anggiat; Napitupulu, Ilham Hidayah; Susilawati , Susilawati (P3M Politeknik Negeri Bengkalis, 2025)
This study aims to examine the effect of Sales Growth (sales growth ratio), Tax Planning (Tax Retention Rate/TRR), and Tax Avoidance (effective tax rate/ETR) on Firm Value (price to book value/PBV) in non-cyclicals consumer sector companies listed on the Indonesia Stock Exchange for the period 2020-2024. This study uses a quantitative approach with secondary data in the form of annual financial reports. The sample was obtained through purposive sampling, resulting in 39 companies form a total population of 130 companies. Data analysis was performed using multiple linear regression with SPSS Version 25. The results show thae sales growth has a significants positive effect on firm value, while tax planning and tax avoidance have no significant effect. This study contributes to enriching the literature on the determinants of firm value and provides practical implications for investors in evaluating a company’s fundamental performance.